Efficacy and Safety of Albumin-Bound Paclitaxel Compared to Docetaxel as Neoadjuvant Chemotherapy for HER2-Negative Breast Cancer - Lv, Zhi-Dong; Song, Hong-Ming; Niu, Zhao-He; Nie, Gang; Zheng, Shuai; Xu, Ying-Ying; Gong, Wei; Wang, Hai-Bo (Frontiers in Oncology, 2022)
Background Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) as neoadjuvant chemotherapy (NAC) for breast cancer remains controversial. We conducted a retrospective study to compare the efficacy and safety of nab-paclitaxel with docetaxel as neoadjuvant regimens for HER2-negative breast cancer. Methods In this retrospective analysis, a total of 159 HER2-negative breast cancer patients underwent operation after NAC were consecutively analyzed from May 2016 to April 2018. Patients were classified into nab-paclitaxel group (n=79, nab-paclitaxel 260mg/m2, epirubicin 75mg/m2 and cyclophosphamide 500mg/m2) and the docetaxel group (n=80, docetaxel 75mg/m2, epirubicin 75mg/m2 and cyclophosphamide 500mg/m2) according to the drug they received for neoadjuvant treatment. The efficacy and adverse events were evaluated in the two groups. Results The pathological complete response (pCR)(ypT0/isN0) rate was signifcantly higher in nab-paclitaxel group than in docetaxel group (36.71% vs 20.00%; P=0.031). The multivariate analysis revealed that therapeutic drugs, lymph node status, and tumor subtype was the most significant factor influencing treatment outcome. At a median follow-up of 47 months, disease-free survival (DFS) was no significant difference in those assigned to nab-paclitaxel compared with docetaxel (82.28% vs 76.25%; P=0.331). The incidence of peripheral sensory neuropathy in nab-paclitaxel group was higher than that in docetaxel group (60.76% vs 36.25%; P=0.008), while the incidence of arthralgia was observed more frequently in docetaxel group (57.50% vs 39.97%; P=0.047). Conclusions Compared with docetaxel, nab-paclitaxel achieved a higher pCR rate, especially those patients with triple-negative breast cancer or lymph node negative breast cancer. However, there was no significant difference in DFS between the two groups. This study provides a valuable reference for the management of patients with HER2-negative breast cancer.